ОПТИМІЗАЦІЯ ВИТРАТ ПЕРВИННОГО ПАЛИВА НА ЛОКАЛЬНИХ РИНКАХ ЕЛЕКТРОЕНЕРГІЇ В СИСТЕМАХ З ДИЗЕЛЬ-ГЕНЕРАТОРАМИ - Денисюк, С.П.; Бєлоха, Г.С.; Дерев’янко, Д.Г. (Інститут електродинаміки НАН України, Київ, 2023)
Local energy markets represent a separate distribution system with several sources of distributed generation and with its own network-independent operator. The cost of electricity in local systems depends on many criteria. They include the consumption of primary fuel for diesel generators, which depend on their capacity. Equal distribution of power on generators running in parallel leads to an increase in primary fuel consumption. An algorithm for optimizing fuel consumption, which calculates the power distribution of generators connected in parallel, has been developed. These capacities correspond to the minimum value of fuel consumption. The system using three diesel generators and the option of replacing one generator with a solar electric installation was considered. The use of the optimal algorithm allows for reducing the price by an average of 9 to 20% if compared to the uniform distribution. The introduction of a photovoltaic system with a rechargeable battery allowed to increase energy efficiency and reduce the price due to lower running costs of the solar installation. References 10, figures 3, tables 1.